Ezra-Nehemiah and Chronicles—New Insights into the Early History of Samari(t)an–Jewish Relations - Hensel, Benedikt (Religions, 2020)
This article addresses the way the book of Ezra-Nehemiah on one hand and Chronicles on the other reflect the relationship between Samaria and Judah in the postexilic period. With regard to Ezra-Nehemiah, the focus is placed on Ezra 4:1-5, 6-23, 24, which evokes a particular image of the nature of the relationship between Samaria and Judah within the report of the construction of the temple in Ezra 1-6 that can function paradigmatically for the book as a whole. With regard to Chronicles, the focus lies on the theme of cult centralization, which became established in a particular manner through the reception of earlier tradition. The article concludes that both works, each in its own way, call forth critique of Samaria and the Samaritans in order to establish a separate Judean or Jewish group identity. The critique of the two works is dated to the late fourth or early third centuries BCE. As such, both are reckoned among the first witnesses heralding a shift in the perception of Samaria in biblical literature, namely toward a polemical and unequivocally negative perspective attested later in, for example, Josephus.